THE INFLUENCE OF LEADERSHIP AND MOTIVATION OF LECTURER PERFORMANCE IN KOPERTIS REGION III JAKARTA - kasbuntoro, kasbuntoro (STIE Kusuma Negara, 2019)
To achieve the company's goals requires the attitude or behavior of people who are responsible and have the ability and good performance. To realize optimal performance is influenced by several factors, including; leadership and high work motivation. The results of the study suggest that there is a positive influence between leadership on lecturer performance, meaning that the better the leadership, the performance can increase, as well as the influence of motivation on lecturer performance has a positive influence and the simultaneous influence between leadership and motivation on lecturer performance.